2022
DOI: 10.1002/cbic.202200121
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Free Protein Synthesis for the Screening of Novel Azoreductases and Their Preferred Electron Donor

Abstract: Azoreductases are potent biocatalysts for the cleavage of azo bonds. Various gene sequences coding for potential azoreductases are available in databases, but many of their gene products are still uncharacterized. To avoid the laborious heterologous expression in a host organism, we developed a screening approach involving cell-free protein synthesis (CFPS) combined with a colorimetric activity assay, which allows the parallel screening of putative azoreductases in a short time. First, we evaluated different C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Depending on the assay applied, results can be obtained only 5 h after the reaction was started, thus allowing increased flexibility and handling. The capability of cell-free systems for those screening approaches was recently demonstrated by the synthesis and characterization of several novel azoreductases ( Rolf et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the assay applied, results can be obtained only 5 h after the reaction was started, thus allowing increased flexibility and handling. The capability of cell-free systems for those screening approaches was recently demonstrated by the synthesis and characterization of several novel azoreductases ( Rolf et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, high-throughput experimental methods can be applied to validate the simulation results in a synergistic manner. Multiple studies have shown that cell-free protein expression methods can nowadays allow efficient enzyme discovery because they can be directly coupled to an activity assay (Silverman et al 2020 ; Garenne et al 2021 ; Kwon and Jewett 2015 ; Tamiev et al 2021 ; Rolf et al 2019 ; Haslinger et al 2021 ; Rolf et al 2022 ). Moreover, they overcome the time-consuming constraints of working with cells and allow for rapid protein production bypassing most of the cloning, expression, and purification steps (Silverman et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…When using unpurified extract-based systems, endogenous proteins or metabolic pathways may compete with the biocatalytic activity of the target enzyme for substrates and reduce or completely mask its detectable activity. 5,6 In such a case, so-called PURE (protein synthesis using recombinant elements) systems can be used, which consist exclusively of components required for protein biosynthesis. 6 Furthermore, even though comparatively high protein concentrations up to mg mL À1 scale have already been achieved in CFPS systems, 7 the average yields and thus concentrations are significantly lower than in many applications using proteins obtained in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In such a case, so-called PURE (protein synthesis using recombinant elements) systems can be used, which consist exclusively of components required for protein biosynthesis. 6 Furthermore, even though comparatively high protein concentrations up to mg mL À1 scale have already been achieved in CFPS systems, 7 the average yields and thus concentrations are significantly lower than in many applications using proteins obtained in vivo. Typically, CFPS on a smallscale (<100 μL) is followed by further dilution with reaction buffer and substrates for the biocatalytic reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation